Effect of dual-thread, length and insertion angle in orthodontic miniscrews primary stability - an in vitro study - BAYERLY, Issam; KHALIL , Fadi (International Arab Journal of Dentistry (IAJD), 2015)
The aim of the study was to determine the effect of dual-thread, length, and insertion angle on orthodontic miniscrew primary stability, and define the best shape and diameter of miniscrew that can be used to confer the best stability. The study sample consisted of 48 orthodontic miniscrews made of Ti-6Al-4V alloy with 2 shapes, standard and dual-thread, 2 lengths were used: 7 and 8mm. Miniscrews were inserted according to 2 angles (45°, 90°) with respect to bone surface. The maximum insertion torque, the Periotest value and the maximum removal torque were measured. The results showed that the maximum insertion and removal torque were statistically higher while the Periotest values were statistically lower when using the dual-thread, 8mm length, and 90° insertion angle than the regular shape, 7mm length and 45° insertion angle (p <0.01).